Penerapan Kaidah Fikih Larangan Gharar dalam Skema Kerjasama Pemerintah dan Badan Usaha (KPBU) Syariah - Umniati, Wafa (TAWAZUN: Journal of Sharia Economic Law, 2026)
Fatwa DSN Number 156/DSN-MUI/V/2023 regulates the implementation of sharia principles in infrastructure provision activities through the Government and Business Entity Cooperation (KPBU) scheme, particularly in the availability payment mechanism. This fatwa serves as a guideline for the government, business entities, and related parties in conducting transactions to ensure compliance with Islamic law principles and to avoid prohibited elements in muamalah contracts, one of which is gharar, namely uncertainty or ambiguity that may cause harm to one of the parties involved in the contract. This research focuses on analyzing the provisions contained in Fatwa DSN Number 156/DSN-MUI/V/2023, particularly regarding the contents of KPBU documents and their conformity with the principles of contracts from the perspective of fiqh muamalah. This research employs a library research method, conducted through the study of various written sources related to the application of the prohibition of gharar in Islamic financial jurisprudence. The results of the study indicate that the implementation of KPBU based on Fatwa DSN Number 156/DSN-MUI/V/2023 still contains several forms of uncertainty (gharar), particularly related to technical aspects of service implementation, the duration of cooperation, and possible changes in conditions during infrastructure projects. However, such uncertainty does not fall into the category of excessive gharar (gharar katsir), which may invalidate the validity of a contract. The gharar found in this scheme is categorized as minor gharar (gharar yasir), meaning uncertainty that is still tolerable because it does not affect the substance of the contract and does not create injustice for the parties involved. This is in accordance with the fiqh legal maxim al-gharar al-katsir yufsidu al-uqud duna yasirihi.